Combined Orthodontic and Surgical Management for Treatment of Severe Class III Malocclusion with Anterior and Posterior Crossbites - Yahya A. Alogaibi; Fahad F. Alsulaimani; Basem Jamal; Rania Mitwally (Case Reports in Dentistry)
Severe class III malocclusion can be a great challenge, especially in adult patients. This case report describes an adult patient with severe skeletal class III malocclusion and with an obvious maxillary deficiency and mandibular excess causing both anterior and posterior crossbites in addition to a shift in the upper and lower midlines to the left concerning the facial midline. This was complicated by compensatory mechanisms such as the proclination of upper incisors and retroclination of lower incisors. Decompensation of the upper and lower arches was performed combined with upper arch expansion to relieve crowding in the upper arch and correct the posterior crossbite. This was followed by double jaw surgeries, including Le Fort I osteotomy in the maxilla and bilateral sagittal split osteotomy (BSSO) in the mandible. Orthodontic finishing procedures were then used to correct any other dental discrepancies. Remarkable esthetic and functional results were achieved with high patient satisfaction.